2018
DOI: 10.7554/elife.38683
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis for coordination of meiosis and sexual structure maturation in Cryptococcus neoformans

Abstract: In the human fungal pathogen Cryptococcus neoformans, sex can benefit its pathogenicity through production of meiospores, which are believed to offer both physical and meiosis-created lineage advantages for its infections. Cryptococcus sporulation occurs following two parallel events, meiosis and differentiation of the basidium, the characteristic sexual structure of the basidiomycetes. However, the circuit integrating these events to ensure subsequent sporulation is unclear. Here, we show the spatiotemporal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
94
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(106 citation statements)
references
References 46 publications
6
94
1
Order By: Relevance
“…Our results demonstrated that the removal of α identity genes did not markedly impair unisexual filamentation and the expression level of mCherry-tagged Cfl1 in unisexual communities, which is an indicator protein for filamentous development reported previously (Figure 1D) [35]. Similarly, in the α-null mutant, no detectable defect was identified during basidial maturation, based on the basidial maturation score (BMS) assay that allow us to quantitatively evaluate basidial maturation (Figure 1E) [16]. In addition, we showed that the α sex-determination system did not appear to impact meiosis during unisexual reproduction, since the simultaneous deletion of the α sex-determination genes cannot cause evident changes in the spatiotemporal expression of Dmc1 (a meiosis-specific recombinase), a meiosis indicator protein that is highly abundant during meiotic progression (Figure 1F) [36].…”
Section: Resultssupporting
confidence: 63%
See 4 more Smart Citations
“…Our results demonstrated that the removal of α identity genes did not markedly impair unisexual filamentation and the expression level of mCherry-tagged Cfl1 in unisexual communities, which is an indicator protein for filamentous development reported previously (Figure 1D) [35]. Similarly, in the α-null mutant, no detectable defect was identified during basidial maturation, based on the basidial maturation score (BMS) assay that allow us to quantitatively evaluate basidial maturation (Figure 1E) [16]. In addition, we showed that the α sex-determination system did not appear to impact meiosis during unisexual reproduction, since the simultaneous deletion of the α sex-determination genes cannot cause evident changes in the spatiotemporal expression of Dmc1 (a meiosis-specific recombinase), a meiosis indicator protein that is highly abundant during meiotic progression (Figure 1F) [36].…”
Section: Resultssupporting
confidence: 63%
“…To identify the regulon of Vea2, we utilized a high-coverage strand-specific RNA-sequencing analysis to compare whole-genome expression between wild-type and the vea2 Δ mutant at 12 hours after sexual induction, when a majority of genes responsible for early sexual events (such as syngamy) are induced based on our previous study [16]. We identified 54 protein-coding genes that displayed markedly altered expression in the absence of Vea2 (Table S2, log 2 |fold-change| > 1.0, q value < 0.01, TPM (transcripts per million mapped) > 5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations